Comparative Evaluation of Palatal Length, Speech Outcome, and Surgical Complications With Use of Von Langenbeck and Bardach 2 Flap Technique for the Repair of Cleft Palate: A Prospective Randomized Study. Issue 1 (March 2022) - Oswal, Yash A.; Natarajan, Srivalli; Despande, Gaurav S.; Patil, Neha S.
Purpose: Successful closure of cleft palate is no more the sole criteria for determining the success of palatoplasty. Approximating soft palate musculature plays an equally important role. A continuous palate with muscular sling, speech and unhampered maxillary growth are 3 important goals of palatoplasty. The current study compared 2 popular palatoplasty techniques and also focused on other vital secondary parameters which would alter the final outcome of palatoplasty.Methods: Thirty-two primary cleft palate patients with repaired cleft lip ranging from 4 to 30 years were randomly and equally divided into 2 groups. Group A underwent Langenbeck and Group B underwent Bardach palatoplasty. Sommerlad's Intra-Velar Veloplasty was performed in all patients. The patients were evaluated for certain palatal and cleft measurements, speech, and surgical complications. The study also compared impact of cleft severity on speech and complications.Results: All the patients showed improvement in palatal length and speech. Significant palatal lengthening was achieved by Bardach as compared to Langenbeck palatoplasty ( P  = .002). Amongst the various speech parameters so compared Bardach group showed better speech articulation post-operatively ( P  = .020). No significant difference was found between the 2 groups in relation to other speech parameters. Total 4 complications were encountered 2 belonging to each group.Conclusion: Hard palate cleft repair technique plays little role as far as speech outcomes are concerned. It was Intravelar Veloplasty which reestablished the velopharyngeal sphincter and improved the quality of speech. Hence restoring the muscular sling of soft palate using radical dissection should be stressed upon by the surgeons besides the closure of cleft. The current study found few confounding factors such as age, cleft width, and Veau's class which altered the speech outcomes and/or complications of palatoplasty.